Analysis of the competitiveness on pig farming in Tejupilco and Luvianos, Mexico (2006-2018) - Hernández-Martínez, Juvencio (2020)
Introduction. Meat pork production is rank third of all meats in Mexico after beef and broilers. Production is not enough to supply the national consumption and reduce imports. Objective. Analyze the evolution of costs, profitability and competitiveness of pig production in the regions of Tejupilco and Luvianos, located in the South of the State of Mexico. Materials and methods. The investigation was carried out using information from forty backyard and one technificated farms; A Policy Analysis Matrix was used. Matrices were elaborated of technical coefficients, prices of inputs and product and private budgets. Results. Private returns (RP) were at 26% for backyard ones and 43% for technifhicated one, while private cost ratio (RCP) was 0.35 for backyard ones and 0.17 for technical one, thus, greater competitiveness was observed in the latter. Conclusion. Indicators point out these two types of pig farms were profitable in 2018, and were competitives in relation to those obtained in 2006, it was mainly due to movements in constant terms of inputs costs, which decreased and the increase in the price of live pigs, which contributed producers taking actions to be more productive and efficient.